Réponses

2014-08-18T01:41:05+02:00

Salut,

A= 2(x-2)+(x+1)(x+3)

A= 2x - 4 + x² + 3x + x + 3

A= x² + 6x - 1


B= (x-3)[(2x-5)-(x-6)]

B= (x - 3) (2x - 5 - x + 6)

B= (x - 3) (x + 1)

B= x² + x -3x - 3

B= x² - 2x - 3

Voilà ! A+ 

B=(x-3)(2x-5)-(x-3)(x+6).B=(x-3)[(2x-5)-(x+6)].b=(x-3)(2x-5-x-6).B=(x-3)(x-11)
??
A: Vrai et B:faute
2014-08-18T01:42:42+02:00
Salut :) 


A = 2(x - 2) + (x + 1)(x + 3) \\  \\ A = 2x - 4 +  x^{2} + 3x + x + 3 \\  \\ A =  x^{2} + 6x - 1


B = (x - 3)[(2x - 5) - (x - 6)] \\  \\ B = (x - 3)(2x - 5 - x + 6) \\  \\ B = (x - 3)(x + 1) \\  \\ B =  x^{2} + x - 3x - 3 \\  \\ B =  x^{2} - 2x - 3


J'espère t'avoir aidé(e) ! :)
A= 2(x-2)+(x+1)(x+3)

A= 2x - 4 + x² + 3x + x + 3

A= x² + 6x - 1
B=(x-3)(2x-5)-(x-3)(x+6).B=(x-3)[(2x-5)-(x+6)].b=(x-3)(2x-5-x-6).B=(x-3)(x-11)